Ayodhya Dispute and Responses of India’s Islamic Neighbors and Hindu Nationalism in India - Phung Thi Thao, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
India has been noted for its independence movements including the non-cooperation and civil disobedience movements under the leadership of the Indian National Congress in general and Mahatma Gandhi in particular. However, in this South Asian country, there is another kind of nationalism that roots in Hinduism. The objective of the article is to explain the nature of Hindu nationalism in India. To gain this aim, the author is going to implement three tasks including giving a brief overview of the Ayodhya dispute; reporting the reactions from India’s neighbors to the Ayodhya issue; and explaining the relations among the Ayodhya related legal fights and responses from Pakistan and Bangladesh, as well as Hindu nationalism. As a result, the study is helpful to comprehend the politics of India and its nationalism.Received 25th September 2020; Revised 2nd January 2021; Accepted 20th February 2021